“NAME, PLEASE!”: EVIDENCE OF HOTEL FRONT OFFICE CANDIDATES’ ENGLISH - Liliek Soepriatmadji; Teguh Kasprabowo; Artin Bayu Mukti (Media Bina Ilmiah, 2023)
This article is meant to explore 1) the typical styles of English spoken by hotel front office candidates, 2) the errors, 3) the awareness about the importance of English mastered by hotel front office candidates. This is important because they become elements of English skills which are dominant to characterize the candidates’ readiness in the hospitality industry. An elicitation technique was applied to gather the data of the typical styles of English, and a questionnaire was also delivered to the respondents - students of hotel studies of Vocational Faculty - Unisbank, to elaborate information about their awareness of English used in hospitality industry. The findings indicate that the candidates mostly used declaratives and interrogatives, for them to give information, demand information and give service. The pragmatic styles used were to engage for information, offer assistance, seek information, and give directions. Mostly, candidates used neutral expressions with no imposition on the politeness strategy, However, some used politeness markers, and others used indirect expressions. Fifty out of 390 utterances were suspected to be ungrammatical, especially in concord. Fortunately, candidates believed that English is still important to help them improve their communication skill in their future job in hospitality industries